Are human resource practices the key to managing job burnout in New Zealand nurses? Testing a path model - Haar, Jarrod; Mowat, Rebecca M. (Journal of clinical nursing, 2022)
Aim To explore if human resource practices are the key to manage job burnout in nurses. Objective To determine if human resource practices provide more meaningful work to nurses, subsequently leading to enhanced work–life balance and lower job burnout (emotional exhaustion and cynicism). Background Job burnout is a global phenomenon, particularly relevant in the nursing profession due to pressures within the health sector. Job burnout is also a result of nurses not balancing work with their life roles and maintaining meaning in one's work. High‐performance systems are tools that hospital human resource departments can use to increase core employee factors that ultimately reduce the risk of job burnout. Methods Using cross‐sectional data from 114 New Zealand nurses, we tested a path model to distinguish whether human resource practices can influence job burnout, with meaningful work and work–life balance mediating. The data were analysed using structural equation modelling and indirect effects for mediating. This research adhered to the STROBE Statement. Results Human resource practices are positively related to meaningful work and work–life balance, and meaningful work was positively related to work–life balance and negatively related to cynicism. Finally, work–life balance is negatively related to emotional exhaustion and cynicism. Conclusions Given the influence of human resource practices on job burnout is fully mediated by meaningful work and work–life balance, indicating that managing job burnout is best understood via human resource practices enhancing nurses meaning from work and role balance, which subsequently reduces job burnout. Relevance to clinical practice Human resource practices can enhance work factors, such as meaningful work and work–life balance, that can enable nurses to have reduced job burnout. This will help prevent cynicism, exhaustion and will therefore prevent absenteeism, enhance performance and overall aid long‐term employment benefitting not only patients but hospitals.